Systemic inhibition of extracellular signal-regulated kinase (ERK) has a protective effect in neonatal cerebral white matter injury. (7th June 2011) - Thei, L; Hristova, M; Kendall, G; Peebles, D; Miller, F; Kaplan, D; Raivich, G
Abstract : The extracellular signal-regulated kinase (ERK) cascade, a key component of mitogen-activated protein kinase signalling, is important in synaptic plasticity, in mediating mitogenic and trophic effects, as well as for cell proliferation in normal and transformed non-neuronal cells. Here, we explored phosphorylated ERK immunoreactivity (pERK-IR) following hypoxic-ischaemic (HI) insult in postnatal day 7–8 mice (equivalent to approx 31–32 week human gestation) by unilateral carotid artery occlusion, followed by hypoxia (8% O2 /N2 ). Exposure to 30 min HI resulted in massive increase in forebrain pERK-IR followed by strong white matter (WM) damage, but only mild involvement of the overlying cortical grey matter. Mapping for activated pERK revealed a time-clock sequence of cellular events, beginning with periventricular WM axons (15–45 min post HI onset), followed by white and grey matter glia and cortical neurons (1–4 h post HI onset), returning to normal by 8 h. Systemic inhibition of MEK1/2 with SL327 resulted in significant decrease in WM damage. This could point to activated MEK1/2 and ERK as promising targets for therapeutic intervention in neonatal brain damage, and in prevention of periventricular leukomalacia.